Influence of the Role of Agriculture Extension Worker (AEW) Against Farming Group Dynamics In the Dry Land Agricultural Area, West Lombok Regency - Dian Mirawati; L. Wiresapta Karyadi; Hayati Hayati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The dynamism of farmer groups is influenced by internal factors, namely the farmer group itself, and external factors, namely the role of the Agriculture Extension Worker (AEW). This research was carried out in West Lombok Regency with the criteria of selecting 2 sub-districts in West Lombok Regency which had a larger dry land area compared to other sub-districts, namely Sekotong District and Lembar District; from each sub-district 3, villages were selected with the criteria of having the largest number of farmers, determining selected farmer groups based on criteria. Farmer groups have been registered in the Decree of the Head of the West Lombok Regency Agricultural Service and have been recorded in the agricultural extension system (simluhtan). This research aimed to analyze the role of AEW, the dynamics of farmer groups, and the influence of the role of Agriculture Extension Worker (AEW) on the dynamics of farmer groups in dryland farming areas in West Lombok Regency. The analytical method used was descriptive analysis with a Likert scale by giving a score of 1-5 for each criterion for each indicator. The research results showed that the respondents' assessment of the role of field agricultural instructors as facilitators, educators, motivators, and organizers was in a good category. Farming group dynamics seen from the aspects of group goals, group structure, task functions, group coaching and development, group cohesiveness, group atmosphere, and group effectiveness was in the quite good category, and the relationship/correlation between the role of AEW and the dynamics of farmer groups was very strong.